Investigation of extractable organic compounds in deep-sea hydrothermal vent fluids along the Mid-Atlantic Ridge. (1st May 2015) - McCollom, Thomas M.; Seewald, Jeffrey S.; German, Christopher R.
Abstract: The possibility that deep-sea hydrothermal vents may contain organic compounds produced by abiotic synthesis or by microbial communities living deep beneath the surface has led to numerous studies of the organic composition of vent fluids. Most of these studies have focused on methane and other light hydrocarbons, while the possible occurrence of more complex organic compounds in the fluids has remained largely unstudied. To address this issue, the presence of higher molecular weight organic compounds in deep-sea hydrothermal fluids was assessed at three sites along the Mid-Atlantic Ridge that span a range of temperatures (51 to >360 °C), fluid compositions, and host-rock lithologies (mafic to ultramafic). Samples were obtained at several sites within the Lucky Strike, Rainbow, and Lost City hydrothermal fields. Three methods were employed to extract organic compounds for analysis, including liquid:liquid extraction, cold trapping on the walls of a coil of titanium tubing, and pumping fluids through cartridges filled with solid phase extraction (SPE) sorbents. The only samples to consistently yield high amounts of extractable organic compounds were the warm (51–91 °C), highly alkaline fluids from Lost City, which contained elevated concentrations of C8, C10, and C12 n -alkanoic acids and, in some cases, trithiolane, hexadecanol, squalene, and cholesterol. Collectively, the C8 –C12 acids can account for about 15% of the total dissolved organic carbon in the Lost City fluids. The even-carbon-number predominance of the alkanoic acids indicates a biological origin, but it is unclear whether these compounds are derived from microbial activity occurring within the hydrothermal chimney proximal to the site of fluid discharge or are transported from deeper within the system. Hydrothermal fluids from the Lucky Strike and Rainbow fields were characterized by an overall scarcity of extractable dissolved organic compounds. Trace amounts of aromatic hydrocarbons including phenanthrenes and benzothiophene were the only compounds that could be identified as indigenous components of these fluids. Although hydrocarbons and fatty acids were observed in some samples, those compounds were likely derived from particulate matter or biomass entrained during fluid collection. In addition, extracts of some fluid samples from the Rainbow field were found to contain an unresolved complex mixture (UCM) of organic compounds. This UCM shared some characteristics with organic matter extracted from bottom seawater, suggesting that the organic matter observed in these samples might represent seawater-derived compounds that had persisted, albeit with partial alteration, during circulation through the hydrothermal system. While there is considerable evidence that Rainbow and Lost City vent fluids contain methane and other light hydrocarbons produced through abiotic reduction of inorganic carbon, we found no evidence for more complex organic compounds with an abiotic origin in the same fluids.